Applying quality by design approach for the determination of potent paclitaxel loaded poly(lactic acid) based implants for localized tumor drug delivery - BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
In the present study, poly(lactic acid) (PLA) and poly(ethylene succinate) (PESu) or poly(ethylene glycol) (PEG) under the framework of quality by design, were blended to produce effective sustained-release matrices for Paclitaxel delivery. A complete physicochemical characterization including weight variation, thickness, water uptake, moisture absorption, moisture loss, and hydrolytic degradation under physiological conditions, was performed. Quality by design approach was applied to study the critical parameters. In vitro cancer toxicity was studied in human cancer cell lines including lung and breast adenocarcinoma. The developed Paclitaxel-loaded films can act as a promising alternative topical matrix as an implant for breast and lung cancer treatment.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; MALZEME BİLİMİ, BİYOMATERYAL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); POLİMER BİLİMİ; Temel Bilimler (SCI); MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Biyomalzemeler; Malzeme Bilimi (çeşitli); Polimerler ve Plastikler; Kimya (çeşitli); Genel Malzeme Bilimi; Genel Kimya; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); Polymers and Plastics; Chemistry (miscellaneous); General Materials Science; General Chemistry; Physical Sciences; Breast cancer; cancer treatment; film; lung cancer; paclitaxel; quality by design; CONTROLLED-RELEASE FORMULATIONS; IN-VITRO; POLY(ETHYLENE SUCCINATE); BLENDS; NANOPARTICLES; FILMS; SYSTEM; CRYSTALLIZATION; BIOAVAILABILITY; PLASTICIZERS